Integrated molecular characterization of IDH‐mutant glioblastomas. (15th November 2018) - Korshunov, A.; Casalini, B.; Chavez, L.; Hielscher, T.; Sill, M.; Ryzhova, M.; Sharma, T.; Schrimpf, D.; Stichel, D.; Capper, D.; Reuss, D. E.; Sturm, D.; et al.
Abstract: Aims: Mutations of isocitrate dehydrogenase (IDH)1/2 affect almost all astrocytomas of WHO grade II and III. A subset of IDH ‐mutant astrocytic tumours progresses to IDH ‐mutant glioblastoma or presents with the histology of a glioblastoma at first presentation. We set out here to assess the molecular spectrum of IDH ‐mutant glioblastomas. Methods: We performed an integrated molecular analysis of a mono‐centric cohort ( n = 97); assessed through genome‐wide DNA methylation analysis, copy‐number profiling and targeted next generation sequencing using a neurooncology‐tailored gene panel. Results: Of these 97 IDH ‐mutant glioblastomas, 68 had a glioblastoma at first presentation (' de novo ' IDH ‐mutant glioblastoma) and 29 emerged from a prior low‐grade lesion ('evolved' IDH ‐mutant glioblastoma). Unsupervised hierarchical clustering of DNA methylation data disclosed that IDH ‐mutant glioblastoma (' de novo ' and 'evolved') formed a distinct group separate from other diffuse glioma subtypes. Homozygous deletions of CDKN2A/B were found to be associated with shorter survival. Conclusions: This study demonstrates DNA methylation patterns in IDH ‐mutant glioblastoma to be distinct from lower‐grade astrocytic counterparts but homogeneous within de novo and evolved IDH ‐mutant glioblastomas, and identifies CDKN2A as a marker for possible genetic sub‐stratification.